Relations between the use of amphetamines and psychotic symptoms: a systematic review - Mesquita, Vinícius Henrique; Rambaldi, Raquel Henriques; Proença, Raquel Lautenschlager Santana (Revista de Medicina, 2022)
Amphetamines are substances which act in the central and peripheral nervous system, with potential to cause intense damage and initiate psychotic symptoms (delusions, hallucinations). This review had as it’s objetive identifying works with essential informations in order to understand the relations between the use of these substances by individuals and the development of psychotic conditions, both transient, happening only during use, and persistent, during and after abstinence, or when evolving to primary disorders, like schizophrenia. Through research in two databases, it was possible to select references that fullfilled the goals. Different researches sought to unravel the action mechanisms of these drugs, and the neurologicsl, biochemical, physiological and molecular bases of psychotic disorders, looking for evidence of connections between the three situations described previously, and significant similatities between the conditions were identified, including in neuroimaging exams and analysis of clinical presentations, besides statistical evidence. However, future studies are necessary to clarify some aspects of this topic and improve the etiological, clinical and diagnostic classification, plus the treatment of these patients.